2015 regionalized social accounting matrix for Tunisia: A nexus project SAM - Salhine, Rim Ben; Younes, Anis Ben; ElKadhi, Zouhair; Jebali, Belhassen; Raouf, Mariam (International Food Policy Research Institute, 2020)
A Social Accounting Matrix (SAM) is an accounting framework that gives a quantitative overview of the structure of the economy over a given time period. It records all transactions between economic agents, while respecting the principles of circularity of flows and balance between revenues and expenditures for each account. The level of disaggregation of accounts in the matrix varies according to the analyses to be undertaken and data availability. The accounts in a national SAM generally are production activities, commodities, institutions, and factors of production. For economic analyses and planning, a more detailed SAM is constructed. These involve disaggregation of activities, households, and factors of production from the more general national SAM. In such matrices, the national economy often will also be disaggregated into sub-national regions. Such SAMs provide rich datasets to help decision-makers in developing, designing, and evaluating regional economic and investment policies. As part of the technical cooperation within the (Arab) Agricultural Investment Development Analyzer (AIDA) project, which aims to develop tools for planning and evaluating investment projects in the agricultural sector, the Institut Tunisien de la Compétitivité et des Etudes Quantitatives (ITCEQ – the Tunisian Institute of Competitiveness and Quantitative Studies), in collaboration with the International Food Policy Research Institute (IFPRI), have built a regionalized SAM of the Tunisian economy with detailed disaggregation at the sector, product, household, and regional levels. This SAM has been constructed using IFPRI's Nexus format, which uses common data standards, procedures, and classification systems for constructing and updating national SAMs. The regionalized SAM for Tunisia was built using national accounts statistics for the country, the Supply and Use Tables for 2015, which are produced by the National Institute of Statistics (NIS). The regionalized matrix is constructed in three steps – national, household, and regional. • The national 2015 SAM for Tunisia includes 46 sectors and 46 products. • For the household SAM, factors of production are split into 13 categories. Capital is disaggregated into four subcategories: crops, livestock, mining, and other. Land is a separate factor of production category. Labor is disaggregated into four education-level categories and across rural and urban areas. For the household SAM, household accounts are split into 15 categories by rural farm, rural nonfarm, and urban categories and then by national per capita expenditure quintiles. • For the regionalized SAM, sectoral production, production factors, and household groups are disaggregated into seven subnational regions: Greater Tunis, North East, North West, Center East, Center West, South East, and South West. The regional 2015 SAM in total has 105 household groups and is composed of 513 rows x 513 columns.